Olprinone attenuates the acute inflammatory response and apoptosis after spinal cord trauma in mice. - Emanuela Esposito; Emanuela Mazzon; Irene Paterniti; Daniela Impellizzeri; Placido Bramanti; Salvatore Cuzzocrea (PLoS ONE, 2010)
BACKGROUND: Olprinone hydrochloride is a newly developed compound that selectively inhibits PDE type III and is characterized by several properties, including positive inotropic effects, peripheral vasodilatory effects, and a bronchodilator effect. In clinical settings, olprinone is commonly used to treat congestive cardiac failure, due to its inotropic and vasodilating effects. The mechanism of these cardiac effects is attributed to increased cellular concentrations of cAMP. The aim of the present study was to evaluate the pharmacological action of olprinone on the secondary damage in experimental spinal cord injury (SCI) in mice. METHODOLOGY/PRINCIPAL FINDINGS: Traumatic SCI is characterized by an immediate, irreversible loss of tissue at the lesion site, as well as a secondary expansion of tissue damage over time. Although secondary injury should be preventable, no effective treatment options currently exist for patients with SCI. Spinal cord trauma was induced in mice by the application of vascular clips (force of 24 g) to the dura via a four-level T5-T8 laminectomy. SCI in mice resulted in severe trauma characterized by edema, neutrophil infiltration, and production of inflammatory mediators, tissue damage, apoptosis, and locomotor disturbance. Olprinone treatment (0.2 mg/kg, i.p.) 1 and 6 h after the SCI significantly reduced: (1) the degree of spinal cord inflammation and tissue injury (histological score), (2) neutrophil infiltration (myeloperoxidase activity), (3) nitrotyrosine formation, (4) pro-inflammatory cytokines, (5) NF-kappaB expression, (6) p-ERK1/2 and p38 expression and (7) apoptosis (TUNEL staining, FAS ligand, Bax and Bcl-2 expression). Moreover, olprinone significantly ameliorated the recovery of hind-limb function (evaluated by motor recovery score). CONCLUSIONS/SIGNIFICANCE: Taken together, our results clearly demonstrate that olprinone treatment reduces the development of inflammation and tissue injury associated with spinal cord trauma.